Ubiquitination and Proteolysis of Cancer-Derived Smad4 Mutants by SCF(Skp2) - Liang, Min (American Society for Microbiology, 2004)
Smad4/DPC4, a common signal transducer in transforming growth factor beta (TGF-β) signaling, is frequently inactivated in human cancer. Although the ubiquitin-proteasome pathway has been established as one mechanism of inactivating Smad4 in cancer, the specific ubiquitin E3 ligase for ubiquitination-mediated proteolysis of Smad4 cancer mutants remains unclear. In this report, we identified the SCF(Skp2) complex as candidate Smad4-interacting proteins in an antibody array-based screen and further elucidated the functions of SCF(Skp2) in mediating the metabolic instability of cancer-derived Smad4 mutants. We found that Skp2, the F-box component of SCF(Skp2), physically interacted with Smad4 at the physiological levels. Several cancer-derived unstable mutants exhibited significantly increased binding to Skp2, which led to their increased ubiquitination and accelerated proteolysis. These results suggest an important role for the SCF(Skp2) complex in switching cancer mutants of Smad4 to undergo polyubiquitination-dependent degradation.